The Adaptive Market Hypothesis：An empirical study on the UK stock market - WANG, KAIXIN (2019)
This paper uses the FTSE 350 daily data and subsample method to detect the Adaptive Market Hypothesis (AMH) in the UK stock market. We performed a range of linear and nonlinear tests on sixteen two-yearly subsamples to capture the time-varying characteristic of market efficiency from 1987 to 2018. Both linear and nonlinear test results provide evidence that the market efficiency is not an all-or-nothing condition, and stock returns experience predictable and unpredictable periods. In addition, we find there is a downward trend for the January effect in the UK stock market during the sample period. Meanwhile, the analysis result suggests that AMH based on its more realistic assumptions provides a better explanation of the January effect than the Efficient Market Hypothesis.